2017
DOI: 10.35808/ersj/661
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Performance of Islamic Banking is better? Panel Data Estimation

Abstract: The global financial crisis has had a negative impact on the banking sector, especially the banking sector in Indonesia. Many studies suggest that Islamic banking is not affected by the global crisis, due to differences in the business nature. The purpose of this study was to analyze the internal and external factors affecting the performance of Islamic banking in Indonesia. This study will also analyze the effect of the global crisis on the financial performance of Islamic banks. This research resulted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 22 publications
3
58
2
7
Order By: Relevance
“…Although banks may have a high rate of NPF, Islamic banks in Indonesia have other income sources that can cover bank losses due to high NPF. The results of this study rejected the findings of Purbaningsih (2014) and Setyawati et al, (2017) who found that NPF had a negative effect on the bank's performance.…”
Section: Results/findingscontrasting
confidence: 97%
“…Although banks may have a high rate of NPF, Islamic banks in Indonesia have other income sources that can cover bank losses due to high NPF. The results of this study rejected the findings of Purbaningsih (2014) and Setyawati et al, (2017) who found that NPF had a negative effect on the bank's performance.…”
Section: Results/findingscontrasting
confidence: 97%
“…Risk is one of the factors that affect the firm's value, the risk of affecting the firm's value through cash flow (Damodaran, 2006;Lusht, 1977), and also throughcompany costs such as agency cost (Petacchi et al, 2012;Naito and Laux 2011;Stulz, 2002), the compensation of the managers, a decrease in the cost of financial distress and bankruptcy and lack of investment management (Bartram, 2006;Carter, Rogers et al, 2006;Bartram and Bodnar, 2007;Bartram et al, 2009;Aretz and Bartram, 2010;Allayannis et al, 2012;El-Charami, 2014;Thalassinos and Politis, 2011;Thalassinos et al, 2012;Setyawati et al, 2017;Glavina, 2015). The previous studies on the effect of risk on the firm's value, carried out in a variety of topics.…”
Section: Business Risk and Firm's Valuementioning
confidence: 99%
“…On another hand, some empirical literature indicates that the Islamic banks' stability is worse than conventional banks because moral hazard and asymmetric information bear on the profit-and-loss sharing system (Kabir, Worthington, & Gupta, 2015;Lassoued, 2018). Volume 24, Issue 1, January 2020: 40-52 | 42 | 2016; Setyawati et al 2017;Sriyana, 2015;Widarjono, 2018;Risfandy, 2018;Octavio & Soesetio, 2019), efficiency of Islamic banks (Hosen & Rahmawati 2016;Aisyah & Hosen, 2018;Majdina, Munandar, & Effendi, 2019) and credit risk of Islamic banks (Firmansyah, 2015;Husa & Trinarningsih, 2015;Nugraheni & Muhammad, 2019). Our present study examines Islamic banks' financial stability in Indonesia.…”
Section: Introductionmentioning
confidence: 99%